Silencing of WNK2 is associated with upregulation of MMP2 and JNK in gliomas - Costa, Angela Margarida (2015)
Matrix metalloproteinases (MMPs) are proteolytic enzymes that degrade extracellular matrix (ECM), thus assisting invasion. Upregulation of MMPs, frequently reported in gliomas, is associated with aggressive behavior. WNK2 is a tumor suppressor gene expressed in normal brain, and silenced by promoter methylation in gliomas. Patients without WNK2 exhibited poor prognosis, and its downregulation was associated with increased glioma cell invasion. Here we showed that MMP2 expression and activity are increased in glioma cell lines that do not express WNK2. Also, WNK2 inhibited JNK, a process associated with decreasing levels of MMP2. Thus, WNK2 promoter methylation and silencing in gliomas is associated with increased JNK activation and MMP2 expression and activity, thus explaining in part tumor cell invasion potential.